PELAKSANAAN PASAL 3 PERATUAN MENTERI LINGKUNGAN HIDUP DAN KEHUTANAN NOMOR P.39 TAHUN 2017 TENTANG PERHUTANAN SOSIAL DI WILAYAH KERJA PERUM PERHUTANI (Studi Di Dinas Kehutanan Kabupaten Tulungagung) - Aria Andrea S. (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Aria Andrea S, Lutfi Effendi, Amelia Ayu Paramitha Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 MalangEmail : ariaandrea1903@yahoo.comAbstrack The implementation of granting permit of the Utilization of Social Forestry (IPHPS) in Working Area of Perum Perhutani is regulated in Article 3 of Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.39 of 2017 on Social Forestry in Working Area of Perum Perhutani that given in the form of Permit of the Utilization of Social Forestry (IPHPS) in the protected and production forest areas. Based on the result of the research, the implementation of Article 3 of Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.39 of 2017 on Social Forestry in Working Area of Perum Perhutani shows that the regulation was not well implemented and it needs some flexibility again to ensure the regulation implemented smoothly with good results.Keywords : Implementation, Permit for Utilization of Social Forestry Forests (IPHPS), Working Area of Perum Perhutani.Abstrak Pelaksanaan pemberian Izin Pemanfaatan Hutan Perhutanan Sosial (IPHPS) pada Wilayah Kerja Perum Perhutani diatur dalam Pasal 3 Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.39 Tahun 2017 Tentang Perhutanan Sosial Di Wilayah Kerja Perum Perhutani, dalamÂ bentuk Izin Pemanfaatan Hutan Perhutanan Sosial (IPHPS) di wilayah Hutan Lindung dan Hutan Produksi. Berdasarkan hasil penelitian, pelaksanaan Pasal 3 Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.39 Tahun 2017 Tentang Perhutanan Sosial Di Wilayah Kerja Perum Perhutani menunjukkan belum sepenuhnya berjalan dengan baik dan dibutuhkan beberapa penyesuaian lagi agar dapat berjalan dengan baik dan lancar.Kata Kunci : Pelaksanaan, Izin Pemanfaatan Hutan Perhutanan Sosial (IPHPS), Wilayah Kerja Perum Perhutani.